Development of Google Sites Problem-Based Learning Differentiated on Biodiversity Materials to Improve Students Interest and Concept Understanding - Kuswandi, Paramita Cahyaningrum; Nisa, Khoirun; Arsyada, Tasya (Universitas Syiah Kuala, 2025)
Learning biodiversity in biology education often presents challenges because the concepts are abstact and difficult to connect with real-life contexts. Coventional learning media generally lack interactivity and fail to accommodate diverse student needs, resulting in low engagement and limited conceptual understanding. Therefore, this study aims to develop, validate, and evaluate the effectiveness of google sites-based learning media integrated with a differentiated problem-based learning (PBL) model for biodiversity material. The research employed the RD method, utilizing the ADDIE model, with 72 students from SMA Negeri 1 Sewon, divided into experimental (X-9) and control (X-10) classes. Data were collected through interviews, needs analysis, validation by experts, teacher and student assessments, concept understanding tests, and learning interest questionnaires. Data analysis employed descriptive techniques and Manova. The results indicated that the developed google sites-based PBL media is highly feasible, practical, and effective. Expert validation confirmed that the content aligns with competencies and learning objectives, presented through structured materials and user friendly design. Teachers and students reported positive responses toward its practicality and engagement. The integration of differentiated instruction within the PBL framework significantly enhanced students learning interest and conceptual understanding. Therefore, google sites-based PBL media can serve as an innovative and inclusive digital learning tool that supports meaningful and active biology learning experiences